The Influence of Reading Interest and English Vocabulary Mastery on the Ability to Read Islamic Texts in the English for Islamic Studies Course - Jumatriadi, Jumatriadi; Satria, Ozi (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study investigates the individual and combined effects of reading interest and vocabulary mastery on students' ability to read Islamic texts in the English for Islamic Studies course. A quantitative correlational design was employed, involving 26 third-semester students from the Islamic Education Program at STIT Palapa Nusantara, selected through purposive sampling. Data were gathered using structured questionnaires assessing reading interest, vocabulary mastery, and Islamic text reading ability, and were analyzed using descriptive statistics and multiple linear regression via SPSS. The results revealed a significant positive correlation between reading interest and Islamic text reading ability (r = 0.574, p < 0.01), with an even stronger correlation between vocabulary mastery and reading ability (r = 0.639, p < 0.01). Descriptive statistics indicated high mean scores across variables, with reading ability (M = 83.7) ranking highest, followed by vocabulary mastery (M = 81.5) and reading interest (M = 78.3). Key performance indicators included interpreting Qur'anic texts (M = 84.2), summarizing Islamic readings (M = 83.1), and understanding basic Islamic concepts (M = 81.6). Multiple regression analysis confirmed that both reading interest (β = 0.401) and vocabulary mastery (β = 0.489) significantly predicted reading ability (p < 0.01), collectively accounting for 53.2% of the variance (R² = 0.532). The findings suggest that enhancing students’ vocabulary and fostering reading interest are effective strategies to improve their comprehension of Islamic texts in English.